(untitled) (Texas Journal of Engineering and Technology, 2025)
In the context of rapid digitalization of public administration, increasing attention is being paid to innovative technologies that can ensure transparency, security, and efficiency in the delivery of public services. One of the most promising technologies is blockchain, which possesses unique characteristics such as decentralized architecture, immutability of data, a high level of trust, and robust information security. This paper explores the international experience of implementing blockchain-based solutions in government and municipal services, using the cases of Estonia, Georgia, the United Arab Emirates, Sweden, and Brazil. The study analyzes the main application areas of the technology, including land and civil registries, e-voting, management of social benefits, and public budget oversight. Particular attention is given to the prospects for adapting these practices in transition economies. The findings underscore the strategic importance of blockchain as a tool for enhancing the effectiveness of public governance, strengthening citizen trust, and optimizing administrative processes. The results can be used in the formulation of national digital strategies in countries with a similar level of digital maturity.